The Influence of Education on Knowledge of the Role of Breastfeeding Fathers at the Ob-Gyn Polyclinic, RSU Balimed Negara - Krisna Dewi, Gusti Ayu; Pramita Aswitami, Ni Gusti Ayu; Yunita Udayani, Ni Putu Mirah (Journal of Ageing And Family, 2023)
The role of the father is critical to the success of breastfeeding. Good knowledge of the role of breastfeeding fathers obtained through education will enable fathers to provide optimal support to mothers in order for them to provide exclusive breastfeeding to their children. The purpose of this study is to determine the effect of education on knowledge of the role Father’s Role in Exclusive Breastfeeding at the Obgyn Polyclinic of RSU Balimed Negara. The study design used was pre-experimental using a one-group pre-post test design. The sampling technique uses nonprobability sampling, namely a total sampling of 32 respondents. The results showed that before the intervention was given, most of the respondents had sufficient knowledge, namely 19 respondents (59.4%) and after the intervention was given, most of the respondents had good knowledge, namely 18 respondents (56.2%). The results of the Wilcoxon signed ranks test obtained a p value (0.000)